Abortion: The Right to an Argument - Meilaender, Gilbert (The Hastings Center report, 1989)
Our moral puzzles about abortion will not be resolved by resort to compromise positions and adoption of middle ground, for abortion concerns how we understand ourselves as a people and how we define membership in this community.